Mining indigenous territories: Consensus, tensions and ambivalences in the Salar de Atacama - Lorca, Mauricio (2022)
Lithium mining in Chile´s Salar de Atacama (SdA) has a relatively long and controversial history, especially when it comes to the local Indigenous peoples. In this context, this paper looks at the ways mining activities, and different visions of territory and indigeneity co-produce each other in the particular context of the SdA. For this, we use historical and ethnographic methods and draw on studies in anthropology and geography. We aim to escape simplistic images of Indigenous peoples'reactions to mining as reflecting victimhood, resistance, or strategic pragmatism, and show instead how individuals and groups organize and express themselves in ambivalent ways, maintaining complex relationships with both mining and the territory. According to our local interlocutors, struggles around territory in the SdA mainly concern water scarcity, the survival of this unique ecosystem´s biological diversity, as well as continuity and change in local lifeways. While recent agreements between mining companies and local communities may benefit some individuals, they are also generating inter- and intra- community tensions over these issues. We find that mining shapes what ´indigenous´ means and who can claim this identity, while Indigenous mobilization in turn shapes how mining is perceived and carried out. Together, mining and Indigenous mobilization produce a particular kind of territory, pervaded by diverse lines of both consensus and tension. Rather than contradictions, the ambivalent positions Indigenous peoples maintain become comprehensible when considering, ethnographically and historically, the particular places and lifeworlds they inhabit, and the asymmetrical patterns of constraint and opportunity they face. More broadly, the paper raises questions about the implications of a global transition to renewable energy based on lithium battery technologies, and ethical responses to the climate crisis.